1999
DOI: 10.1046/j.1463-5224.1999.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Doppler imaging of the ophthalmic vasculature in normal Beagles and Beagles with inherited primary open‐angle glaucoma

Abstract: The objective of this study was to compare orbital and ocular vasculature velocity, measured by Doppler imaging, in normal Beagles and Beagles with inherited primary open-angle glaucoma. Eight normal Beagles and 13 Beagles with different stages of primary open-angle glaucoma were evaluated twice with a 2-4-week period between measurements. Doppler imaging was performed with the dogs anesthetized, and the Doppler transducer applied directly on the corneal surface. The majority of the orbital vasculature (extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Retinal artery blood flow velocities were not different in the two groups. 105 Affected beagles investigated with the same modality during a 4-year longitudinal study showed the blood flow abnormalities to be progressive and to occur ahead of increases in IOP. 11 Whether the changes observed in dogs can be translated to humans is uncertain.…”
Section: Vascular Theorymentioning
confidence: 99%
“…Retinal artery blood flow velocities were not different in the two groups. 105 Affected beagles investigated with the same modality during a 4-year longitudinal study showed the blood flow abnormalities to be progressive and to occur ahead of increases in IOP. 11 Whether the changes observed in dogs can be translated to humans is uncertain.…”
Section: Vascular Theorymentioning
confidence: 99%
“…39 Administration of antiglaucoma drugs can also alter blood flow velocities and resistive indices in dogs. Specifically, decreased EDVs and increased RIs were found within their short posterior ciliary arteries (main blood supply to the canine optic disc).…”
Section: Color Doppler Evaluation Of the Ocular And Orbital Vasculaturementioning
confidence: 99%
“…3 Since then, multiple reports on the normal B-mode ultrasonographic appearance of the canine and equine eye have been published. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Radiography, computed tomography (CT), and magnetic resonance imaging (MRI) are other diagnostic imaging modalities capable of providing detailed information about the eye, orbit, and periorbital tissues. In addition, the retrobulbar soft tissues may be imaged.…”
mentioning
confidence: 99%
“…CDI has been reported in normal dogs, 25,26 dogs with several ophthalmic diseases, 27 and in the Beagle with primary open angle glaucoma 28–30 . In the initial report on color Doppler imaging in the dog, the blood flow patterns were grouped into normo‐, hypo‐, hyper‐, or neovascular 27 .…”
Section: Introductionmentioning
confidence: 99%